2013
DOI: 10.1002/app.39356
|View full text |Cite
|
Sign up to set email alerts
|

Identification by GC‐O and GC‐MS of new odorous compounds in natural rubber

Abstract: Natural rubber products emit malodourous compounds, which can contaminate the air and water of the inhabited surroundings of the production factories. Analytical methods such as SPME coupled with GC-MS and GC-O-FID were used to elucidate the composition and olfactory impact of volatile compounds released from two various grades of natural rubber submitted to different coagulation processes. Forty-three volatile compounds were identified and amongst 16 of them that had never been reported. The volatile compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Propionic acid, isobutyric acid, and 3-methylbutyric acid have a certain pungent smell, with a sour and rancid taste. Butyric acid has a rancid, buttery, and cheesy aroma [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Propionic acid, isobutyric acid, and 3-methylbutyric acid have a certain pungent smell, with a sour and rancid taste. Butyric acid has a rancid, buttery, and cheesy aroma [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…But it demonstrated that the abundance of TVOCs in SPR 10# was higher than that in SVR 3L. This difference was caused by the different production methods (coagulation process, drying process) and storage time in rubbers (Juntarachat et al 2013). For example, SVR 3L is prepared from natural latex through ltration and coagulation processes, then drying and packing.…”
Section: Comparison Of Vocs In Resin and Nrmentioning
confidence: 99%
“…Butylated hydroxytoluene (BHT, 14.29 min), a white crystalline substance, was widely used in foods, rubber, and petroleum products (Yehye et al 2015). Previous research has also reported that it is a potential pyrolysis product of sinapic acid in NR (Juntarachat et al 2013). But the results of Table 6 indicated that it is more likely to be added directly to CIIR as an antioxidant (Babich 1982).…”
Section: Identi Cation Of Vocs Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, many researchers have carried out considerable research on VOC composition, low VOC treatment technology and spray-free treatment technology for the preparation of polymers, obtaining some good results in these fields of research. Some researchers used GC-MS, dynamic dilution olfactometry and field of odors method -to identify low molecular weight compounds and odor [5][6][7][8][9][10][11][12][13]. Some researchers investigated the adsorption mechanisms of VOCs on porous polymeric resin, their odor formation mechanisms and the effects of the adsorbent on the VOCs and odor [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%